An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Veres, Andrea; Wyckhuys, Kris A. G.; Kiss, Jozsef; Tóth, Ferenc; Burgio, Giovanni; Pons, Xavier; Avilla, Carlos; Vidal, Stefan; Razinger, Jaka; Bazok, Renata; Matyjaszczyk, Ewa; Milosavljević, Ivan; et al. (Springer, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera) in maize; wireworms (Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid (Rhopalosiphum padi) in winter wheat; brown planthopper (BPH, Nilaparvata lugens) in rice; cotton aphid (Aphis gossypii) and silver-leaf whitefly (SLW, Bemisia tabaci) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.